Nitrogen-doped carbon-coated cobalt zinc carbide catalyst material as well as preparation method and application thereof
By using nitrogen-doped carbon to coat cobalt-zinc carbide catalyst material on the lithium-sulfur battery separator, the problem of insufficient cycle stability of lithium-sulfur battery is solved, and efficient utilization of sulfur active substances and electrochemical performance improvements are achieved.
Patent Information
- Application Number
- CN202411282985.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-03-28
AI Technical Summary
Existing lithium-sulfur batteries have insufficient cycle stability, fast capacity decay and safety problems, which limit their practical applications.
Nitrogen-doped carbon-cobalt-carbide zinc catalyst material is used as the separator modification material. Through bimetallic synergistic effect and the utilization of biomass precursors, catalyst materials with high dispersion active sites, rich porous structures and high conductivity are prepared, and commercial separators are modified to improve electrochemical performance.
Through physical anchoring and chemical adsorption, the catalyst material weakens the bonding of Li-S bonds, promotes the formation of "metal-sulfur" bonds, improves the cycle stability and electrochemical performance of lithium-sulfur batteries, and achieves the efficient utilization of sulfur active substances.
Smart Images

Figure CN119725988A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano-catalytic materials and lithium-sulfur batteries, and specifically relates to a nitrogen-doped carbon-coated cobalt zinc carbide catalyst material and a preparation method and application thereof. Background Art
[0002] With the continuous development and progress of human society, the basic energy that is overly dependent on non-renewable resources such as fossil fuels is facing challenges from various factors, including the increasing demand for fossil fuels and the shortage of some non-renewable resources. Therefore, in the face of the above problems, humans have begun to explore cleaner and renewable energy to replace the use of fossil fuels. Among them, electric energy, as a landmark product of the second industrial revolution of mankind, not only has the advantages of cleanliness and renewable, but also has the advantages of more economical and safe transmission and easier conversion into other forms of energy, making the development and use of electric energy a more reasonable solution for replacing the use of non-renewable energy. Therefore, the development of electrochemical systems (such as batteries, capacitors, etc.) that can make better use of and store electric energy has become one of the current hot research topics in various countries.
[0003] Rechargeable batteries are the most economical and feasible choice in electrochemical systems. Among them, lithium-ion batteries can provide high energy density and have always been a hot research topic. At present, the use of commercial lithium-ion batteries dominates the market. However, the development of traditional commercial lithium-ion batteries has basically reached the theoretical energy limit, and the insertion of composite cathodes (such as LiCoO 2 、LiMn 2 O 4 、LiFePO 4 The cost will be higher, which cannot meet the needs of the ever-changing electronic equipment, and also cannot meet the needs of the emerging energy storage equipment for higher energy density and longer cycle life. Compared with lithium-ion batteries, lithium-sulfur batteries have higher specific capacity (1675mA hg -1 ) and energy density (2600Wh kg -1 ), and cheap, non-toxic sulfur resources as the cathode, making it one of the most promising next-generation power devices.
[0004] Low-cost electrode materials, high theoretical specific capacity and high theoretical energy density make lithium-sulfur batteries one of the most promising battery systems at present. However, problems such as insufficient cycle stability, rapid capacity decay and safety limit their practical application. The main problems of lithium-sulfur batteries are as follows: (1) poor conductivity of sulfur and lithium sulfide; (2) poor solubility of lithium polysulfide; (3) volume expansion effect; (4) safety issues of lithium metal anode; (5) electrolyte safety issues, etc. The above problems restrict the promotion and application of lithium-sulfur batteries.
[0005] In response to the above problems, how to design a reasonable structure to alleviate the internal volume expansion during the electrochemical reaction and excellent catalytic ability to quickly adsorb, bind and convert polysulfides has become the key to lithium-sulfur battery research, and commercial diaphragm modification layer catalysts are one of the main research directions at present.
[0006] For example, the patent application with the patent application number: 202110063670.8 discloses a method for preparing a modified diaphragm material for lithium-sulfur batteries. The preparation method comprises: selecting a two-dimensional sheet material with high conductivity and high catalytic activity as a template, coating a layer of ionic polymer on its surface through the Schiff base reaction of triaminoguanidine hydrochloride and 1,3,5-triformylphloroglucinol, and then mixing it with polyvinylidene fluoride to obtain a dispersion and coating it on the diaphragm substrate, and drying it to obtain the modified diaphragm for lithium-sulfur batteries. The sheet material coated with an ionic polymer on the diaphragm of the present invention can accelerate the reaction kinetics of the diaphragm intercepting polysulfide through the mode of electrostatic adsorption-rapid diffusion-catalytic conversion, avoid the deposition of solid products on the diaphragm, and achieve high electrochemical performance under high sulfur content and high sulfur loading conditions. However, the preparation method of the modified material has the following disadvantages: 1. Complex preparation process: The method involves multiple steps, such as the preparation of two-dimensional sheet materials, the reaction of triaminoguanidine hydrochloride and 1,3,5-triformylphloroglucinol, the coating of ionic polymers, and the mixing and coating with polyvinylidene fluoride. These steps increase the complexity of the process and may bring operational challenges and increase production costs.
[0007] 2. Material selection limitations: The selected two-dimensional sheet materials need to have high conductivity and high catalytic activity, which places high demands on the selection and preparation of materials, limits the types of applicable materials, and may also increase material costs.
[0008] 3. Stability and uniformity of preparation: During the coating process, the uniformity and stability of the ionomer may be difficult to control, which may result in uneven coating or inconsistent performance, thus affecting the overall performance of the battery.
[0009] 4. Environmental and safety issues: The use of triaminoguanidine hydrochloride and 1,3,5-triformylphloroglucinol may involve certain environmental and safety issues, and these chemicals need to be strictly controlled and handled during the production process.
[0010] 5. Technical complexity and cost issues: Due to the involvement of multiple materials and complex process steps, the method has high technical complexity, which may lead to an increase in overall cost, which may become a limiting factor in large-scale production. Summary of the invention
[0011] Based on the above technical background, the main purpose of the present invention is to provide a nitrogen-doped carbon-coated cobalt zinc carbide catalyst material and its preparation method and application to overcome the shortcomings in the prior art. The present invention mainly utilizes the bimetallic synergistic effect and biomass precursor to prepare a nitrogen-rich doped porous carbon composite material with highly dispersed active sites, rich porous structure and high conductivity, and coats and modifies the traditional commercial PP diaphragm. On the one hand, the nitrogen-carbon material coated on the surface of the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material has a rich hierarchical pore structure, which can form an effective physical anchor for lithium polysulfide, and the polar nitrogen atoms can provide a strong chemical adsorption effect, thereby weakening the bonding of the Li-S bond. After the nitrogen-carbon material is compounded with a highly dispersed metal compound (cobalt zinc carbide nanoparticles), the nanoscale metal compound material can provide more abundant chemical active sites, which can promote the formation of "metal-sulfur" bonds to weaken the bonding of polysulfides. On the other hand, the diaphragm modified by the catalyst material of the present invention has better selective permeability while ensuring the original performance, which can effectively alleviate the shuttling of polysulfides and ensure Li + The rapid migration of sulfur-containing materials can achieve the confinement / anchoring of soluble polysulfides on the cathode side and the dynamic rapid "adsorption-conversion-desorption" during the electrochemical process, thereby realizing the efficient utilization of sulfur active substances and greatly improving the performance of lithium-sulfur batteries.
[0012] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0013] The first aspect of the present invention is to provide a nitrogen-doped carbon-coated cobalt zinc carbide catalyst material, wherein the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material is prepared by stirring, standing aging, and high-temperature carbonization of potassium cobalt cyanide, a soluble ortho-divalent cobalt salt, and a soluble ortho-divalent zinc salt;
[0014] The molar ratio of the soluble orthodivalent cobalt salt, the soluble orthodivalent zinc salt and potassium cobalt cyanide is 1:3-8:3-8.
[0015] Preferably, the soluble cobalt salt is selected from Co(NO 3 ) 2 6H 2 O、CoCl 2 6H 2 O、Co(CH 3 COO 2 ·4H 2 One or more of O.
[0016] Preferably, the soluble divalent zinc salt is selected from Zn(NO 3 ) 2 6H 2 O、ZnCl 2 、Zn(CH3 COO 2 ·2H 2 One or more of O.
[0017] The second aspect of the present invention is to provide a method for preparing the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material according to the first aspect of the present invention, the preparation method comprising the following steps:
[0018] Step 1, adding potassium cobalt cyanide into water to obtain liquid A, adding a soluble ortho-divalent cobalt salt and a soluble ortho-divalent zinc salt into water to obtain liquid B, adding liquid B into liquid A, stirring at room temperature, and then standing for aging to obtain a nitrogen-doped carbon-coated cobalt zinc carbide material precursor;
[0019] Step 2: Centrifuge, wash, and vacuum dry the nitrogen-doped carbon-coated cobalt zinc carbide material precursor obtained in step 1, and then 2 High-temperature carbonization is carried out under the protection of atmosphere, and nitrogen-doped carbon-coated cobalt zinc carbide catalyst material is obtained after cooling.
[0020] In step 1,
[0021] Preferably, liquid B is slowly added to liquid A under stirring, with a volume ratio of liquid B to liquid A of 1:1, and stirring is continued at room temperature for 5 to 20 minutes;
[0022] Preferably, the static aging time is 12 to 36 hours, and the static aging temperature is room temperature.
[0023] In step 2,
[0024] Preferably, the vacuum drying temperature is 50-70°C;
[0025] Preferably, the high temperature carbonization conditions are: 2 Under the protection of atmosphere, the temperature is increased to 600-800°C at a rate of 2-5°C / min, and then kept at 600-800°C for 0.5-3h.
[0026] The third aspect of the present invention is to provide an application of the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material described in the first aspect of the present invention in the preparation of a lithium-sulfur battery separator.
[0027] The fourth aspect of the present invention is to provide a lithium-sulfur battery separator, wherein the lithium-sulfur battery separator is made of the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material described in the first aspect of the present invention.
[0028] Preferably, the lithium-sulfur battery separator is prepared by the following steps:
[0029] The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material, the conductive agent and the binder are added into the solvent and stirred evenly, the obtained slurry is evenly coated on the diaphragm, and then vacuum dried to obtain the lithium-sulfur battery diaphragm.
[0030] The beneficial effects of the present invention are:
[0031] (1) The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material of the present invention is prepared from potassium cobalt cyanide, a soluble positive divalent cobalt salt and a soluble positive divalent zinc salt; the catalyst material has a core-shell structure, including a nitrogen-carbon structure and cobalt zinc carbide nanoparticles, wherein the ultra-thin nitrogen-carbon structure is coated on the irregular surface of the cobalt zinc carbide nanoparticles, and the ultra-thin nitrogen-carbon structure not only stabilizes the internal bimetallic carbide nanoparticle structure, but also ensures the LiPSs and Co 3 The bimetallic active sites of ZnC react effectively, so that the catalyst material of the present invention can greatly improve the electrochemical performance of lithium-sulfur batteries as a diaphragm modification functional material of lithium-sulfur batteries.
[0032] (2) The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material of the present invention has a large number of micropores and mesopore structures, which can effectively capture the dissolved lithium polysulfide during the operation of the lithium-sulfur battery. More importantly, the bimetallic carbide of cobalt zinc carbide (cobalt zinc carbide nanoparticles) has abundant active sites of Co and Zn bimetallics, which can achieve efficient catalytic conversion of lithium polysulfide and accelerate the redox reaction rate of lithium polysulfide during the charging and discharging process, thereby facilitating the inhibition of the "shuttle effect" of lithium-sulfur batteries and improving the electrochemical performance of lithium-sulfur batteries. This makes the catalyst material of the present invention have good application prospects in the preparation of lithium-sulfur battery separators.
[0033] (3) The preparation method of the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material of the present invention first adopts a simple one-step coordination reaction to synthesize the precursor material, and then carbonizes it at high temperature to obtain the catalyst. The preparation method is simple and can be industrialized. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The Prussian blue analog precursor (potassium cobalt cyanide) and the Co prepared in Example 1 are shown. 3 X-ray diffraction (XRD) spectrum of ZnC@NC;
[0035] Figure 2 The Co prepared in Example 1 is shown 3 SEM images ((a)-(c)), HR-TEMH images ((d)-(f)) and EDS spectra ((g)-(l)) of ZnC@NC composites;
[0036] Figure 3 The Co prepared in Example 2 is shown 3Comparison of voltage curves of lithium-sulfur batteries assembled from ZnC@NC / PP, SuperP / PP prepared in Comparative Example 1, and PP at the 0.5C first charge and discharge platform;
[0037] Figure 4 The Co prepared in Example 2 is shown 3 Constant current charge-discharge curves of the first charge-discharge and the 100th charge-discharge of the lithium-sulfur battery assembled with ZnC@NC / PP at 0.5C;
[0038] Figure 5 The Co prepared in Example 2 is shown 3 EIS spectrum of the lithium-sulfur battery assembled with ZnC@NC / PP before cyclic charge and discharge (a), and CV curve at a scan rate of 0.1mV / s (b);
[0039] Figure 6 The Co prepared in Example 2 is shown 3 Rate performance test diagram of lithium-sulfur battery assembled with ZnC@NC / PP and PP separator;
[0040] Figure 7 The Co prepared in Example 2 is shown 3 The battery cycle capacity and coulombic efficiency diagram of the lithium-sulfur battery assembled from ZnC@NC / PP, SuperP / PP prepared in Comparative Example 1 and PP at a current density of 0.5C;
[0041] Figure 8 The Co prepared in Example 2 is shown 3 Battery cycling capacity and coulombic efficiency of lithium-sulfur battery assembled with ZnC@NC / PP at 1.0C current density;
[0042] Fig. 9 The Co prepared in Example 2 is shown 3 Cycling capacity and coulombic efficiency of high-load (poor electrolyte) lithium-sulfur batteries assembled with ZnC@NC / PP at current densities of 0.2C and 0.5C. DETAILED DESCRIPTION
[0043] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the description.
[0044] The first aspect of the present invention is to provide a nitrogen-doped carbon-coated cobalt zinc carbide catalyst material, wherein the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material is prepared from potassium cobalt cyanide, a soluble orthodivalent cobalt salt and a soluble orthodivalent zinc salt.
[0045] The molar ratio of the soluble orthodivalent cobalt salt, the soluble orthodivalent zinc salt and potassium cobalt cyanide is 1:3-8:3-8.
[0046] Preferably, the molar ratio of the soluble orthodivalent cobalt salt, the soluble orthodivalent zinc salt and potassium cobalt cyanide is 1:5:4.
[0047] The soluble cobalt salt is selected from Co(NO 3 ) 2 6H 2 O、CoCl 2 6H 2 O、Co(CH 3 COO 2 ·4H 2 One or more of O.
[0048] Preferably, the soluble cobalt salt is Co(NO 3 ) 2 6H 2 O.
[0049] The soluble positive divalent zinc salt is selected from Zn(NO 3 ) 2 6H 2 O、ZnCl 2 、Zn(CH 3 COO 2 ·2H 2 One or more of O.
[0050] Preferably, the soluble divalent zinc salt is Zn(NO 3 ) 2 6H 2 O.
[0051] The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material has a core-shell structure, comprising irregular cobalt zinc carbide nanoparticles and an ultrathin nitrogen-carbon structure coated on the surface thereof.
[0052] The second aspect of the present invention is to provide a method for preparing the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material according to the first aspect of the present invention, the preparation method comprising the following steps:
[0053] Step 1, adding potassium cobalt cyanide into water to obtain liquid A, adding a soluble ortho-divalent cobalt salt and a soluble ortho-divalent zinc salt into water to obtain liquid B, adding liquid B into liquid A, stirring at room temperature, and then standing for aging to obtain a nitrogen-doped carbon-coated cobalt zinc carbide material precursor;
[0054] Step 2: Centrifuge, wash, and vacuum dry the nitrogen-doped carbon-coated cobalt zinc carbide material precursor obtained in step 1, and then 2 High-temperature carbonization is carried out under the protection of atmosphere, and nitrogen-doped carbon-coated cobalt zinc carbide catalyst material is obtained after cooling.
[0055] The above steps are described in detail below.
[0056] In step 1, the amount of water added needs to be able to completely dissolve the soluble ortho-cobalt salt and the soluble ortho-zinc salt. The concentration of the soluble ortho-cobalt salt in liquid B after complete dissolution is 0.005-0.03 mol / L, preferably 0.01 mol / L.
[0057] Slowly add liquid B into liquid A under stirring, with the volume ratio of liquid B to liquid A being 1:1, and continue stirring at room temperature for 5 to 20 minutes, preferably, continue stirring at room temperature for 10 minutes.
[0058] The static aging is carried out at room temperature, and the static aging time is 12 to 36 hours. Preferably, the static aging time is 24 hours.
[0059] In step 2, the vacuum drying temperature is 50-70°C, preferably, the vacuum drying temperature is 60°C.
[0060] The high temperature carbonization conditions are: 2 Under the protection of atmosphere, the temperature is increased to 600-800°C at a rate of 2-5°C / min, and then kept at 600-800°C for 0.5-3h.
[0061] Preferably, the high temperature carbonization conditions are: 2 Under the protection of atmosphere, the temperature was raised to 700°C at a rate of 3°C / min, and then kept at 700°C for 1 h.
[0062] The present invention firstly mixes potassium cobalt cyanide (Prussian blue analogue) with cobalt and zinc salts, and then allows them to stand for aging to form a precursor. 2 High-temperature carbonization is carried out under protection, so that the irregular nanoparticles of cobalt zinc carbide are effectively coated by an ultra-thin nitrogen-carbon layer. The catalyst material prepared by the present invention has a large number of micropores and mesopore structures, which can effectively capture dissolved lithium polysulfide. The coated cobalt zinc carbide bimetallic nanoparticle carbide has abundant active sites of Co and Zn bimetallics, which can not only realize the efficient catalytic conversion of lithium polysulfide, but also accelerate the redox reaction rate of lithium polysulfide during the charging and discharging process, thereby facilitating the inhibition of the "shuttle effect" of lithium-sulfur batteries. The catalyst material is used as a diaphragm modification material and coated on a commercial diaphragm by a doctor blade method. It can be used in lithium-sulfur batteries to effectively improve the electrochemical performance of lithium-sulfur batteries.
[0063] The third aspect of the present invention is to provide an application of the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material described in the first aspect of the present invention in the preparation of a lithium-sulfur battery separator.
[0064] The fourth aspect of the present invention is to provide a lithium-sulfur battery separator, wherein the lithium-sulfur battery separator is made of the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material described in the first aspect of the present invention.
[0065] The lithium-sulfur battery separator is prepared by the following steps:
[0066] The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material, the conductive agent and the binder are added into the solvent and stirred evenly, the obtained slurry is evenly coated on the diaphragm, and then vacuum dried to obtain the lithium-sulfur battery diaphragm.
[0067] Preferably, the lithium-sulfur battery separator is prepared by the following steps:
[0068] Nitrogen-doped carbon-coated cobalt zinc carbide catalyst material, conductive carbon black Super P Li and binder PVDF (polyvinylidene fluoride) are added to N-methylpyrrolidone solvent in a mass ratio of (5-10): 1:1 and stirred for 10-15 hours. The resulting slurry is evenly coated on the diaphragm and then vacuum dried at 50-70°C to obtain a lithium-sulfur battery diaphragm.
[0069] More preferably, the lithium-sulfur battery separator is prepared by the following steps:
[0070] Nitrogen-doped carbon-coated cobalt zinc carbide catalyst material, conductive carbon black Super P Li and binder PVDF (polyvinylidene fluoride) were added to N-methylpyrrolidone solvent in a mass ratio of 8:1:1 and stirred for 12 hours. The resulting slurry was evenly coated on the diaphragm and then vacuum dried at 60°C to obtain a lithium-sulfur battery diaphragm.
[0071] Example
[0072] The present invention is further described below by specific examples, which are limited to illustrating the present invention but not to limiting the scope of the present invention. The raw materials used in the examples of the present invention were all purchased.
[0073] Example 1
[0074] The nitrogen-doped carbon-coated cobalt zinc carbide (Co 3 The preparation method of ZnC@NC) is as follows:
[0075] Take 1.3293g of potassium cobalt cyanide and add it to 100mL of deionized water, labeled as liquid A. Take 0.2920g of Co(NO 3 ) 2 6H 2 O and 1.4875g Zn(NO 3 ) 2 6H 2O was added into 100 mL of deionized water and marked as liquid B. Liquid B was slowly added into liquid A under stirring, and the stirring was continued for 10 min at room temperature, and then aged at room temperature for 24 h to obtain a precursor.
[0076] The pink precursor was centrifuged, washed, dried in vacuum at 60 °C, and placed in a tube furnace under N 2 Under the protection of atmosphere, carbonization was carried out at 700℃ for 1h, with a heating rate of 3℃ / min. After cooling to room temperature, the sample was collected and named Co 3 ZnC@NC.
[0077] Example 2
[0078] The nitrogen-doped carbon-coated cobalt zinc carbide modified diaphragm (Co 3 The preparation method of ZnC@NC / PP) comprises the following steps:
[0079] The Co prepared in Example 1 3 ZnC@NC, conductive carbon black Super P Li and binder PVDF were weighed in a mass ratio of 8:1:1 and stirred for 12 h with N-methylpyrrolidone (NMP) as solvent. The resulting slurry was then coated on one side of the commercial separator Celgard 2500 by a doctor blade method. The separator was then dried in a vacuum oven at 60 °C overnight and the resulting separator was labeled Co 3 ZnC@NC / PP was cut into discs with a diameter of 19 mm, and its loading was about 0.8 mg / cm 2 .
[0080] Example 3
[0081] The nitrogen-doped carbon-coated cobalt zinc carbide (Co 3 The preparation method of ZnC@NC) is as follows:
[0082] Take 1.3293g of potassium cobalt cyanide and add it to 100mL of deionized water, labeled as liquid A. Take 0.2920g of Co(NO 3 ) 2 6H 2 O and 1.4875g Zn(NO 3 ) 2 6H 2 O was added to 100 mL of deionized water and marked as solution B. Solution B was slowly added to solution A under stirring, and the stirring was continued at room temperature for 5 min, and then aged at room temperature for 12 h to obtain a precursor.
[0083] The pink precursor was centrifuged, washed, dried in vacuum at 50 °C, and placed in a tube furnace under N 2Under the protection of atmosphere, carbonization was carried out at 600℃ for 3h, with a heating rate of 2℃ / min. After cooling to room temperature, the sample was collected and named Co 3 ZnC@NC.
[0084] Example 4
[0085] The nitrogen-doped carbon-coated cobalt zinc carbide (Co 3 The preparation method of ZnC@NC) is as follows:
[0086] Take 1.3293g of potassium cobalt cyanide and add it to 100mL of deionized water, labeled as liquid A. Take 0.2920g of Co(NO 3 ) 2 6H 2 O and 1.4875g Zn(NO 3 ) 2 6H 2 O was added to 100 mL of deionized water and marked as liquid B. Liquid B was slowly added to liquid A under stirring, and the stirring was continued at room temperature for 20 min, and then aged at room temperature for 36 h to obtain a precursor.
[0087] The pink precursor was centrifuged, washed, dried in vacuum at 70 °C, and placed in a tube furnace under N 2 Under the protection of atmosphere, carbonization was carried out at 800℃ for 0.5h, with a heating rate of 5℃ / min. After cooling to room temperature, the sample was collected and named Co 3 ZnC@NC.
[0088] Comparative Example 1
[0089] The preparation method of the SuperP / PP modified diaphragm comparison sample of this embodiment, the specific steps are as follows:
[0090] Conductive carbon black Super P Li and binder PVDF were weighed in a mass ratio of 9:1, and N-methylpyrrolidone (NMP) was used as a solvent and stirred for 12 hours. The resulting slurry was then coated on one side of the commercial diaphragm Celgard2500 by a doctor blade method. It was then placed in a vacuum oven at 60°C and dried overnight. The resulting diaphragm was marked as SuperP / PP and cut into discs with a diameter of 19 mm. The loading amount was approximately 0.8 mg / cm 2 .
[0091] Experimental example
[0092] Experimental Example 1 XRD test
[0093] The Prussian blue analog precursor (potassium cobalt cyanide) and the nitrogen-doped carbon-coated cobalt zinc carbide (Co 3ZnC@NC) was subjected to XRD test, and the test results are shown in Figure 1 shown.
[0094] Figure 1 The upper part is the XRD curve of the Prussian blue analog precursor. Figure 1 The above figure shows a series of Zn 3 [Co(CN) 6 ] 2 -(H 2 O) 12 (PDF#89-3739) characteristic diffraction peaks. Figure 1 The lower part is the nitrogen-doped carbon-coated cobalt zinc carbide (Co 3 The XRD curve of ZnC@NC Figure 1 As can be seen from the figure below, there is a peak around 26°, which is the characteristic diffraction peak of carbon. The other characteristic diffraction peaks at 34.0°, 41.9°, 48.8° and 71.5° correspond to Co 3 The (1 1 0), (1 1 1), (2 0 0) and (2 2 0) characteristic planes of ZnC (PDF#29-0524) are confirmed by XRD test. 3 Composition of ZnC@NC composites.
[0095] Experimental Example 2 SEM test and TEM test
[0096] The nitrogen-doped carbon-coated cobalt zinc carbide (Co 3 ZnC@NC) was subjected to SEM and TEM tests. Figure 2 (a)-(c) are SEM images of nitrogen-doped carbon-coated cobalt zinc carbide prepared in Example 1. Figure 2 (d)-(g) are TEM images of nitrogen-doped carbon-coated cobalt zinc carbide prepared in Example 1.
[0097] from Figure 2 (a)-(c) show that Co 3 ZnC@NC composite materials have abundant and fine nanoparticles, and the nanoparticles are densely packed. At the same time, some nanoparticles are connected by fine carbon nanotube structures. Figure 2 In (c), it can be clearly seen that there are fine carbon nanotube connecting structures between the particles.
[0098] Figure 2 In (d)-(g), from Figure 2 (d) It can be seen that the Co prepared in Example 1 3 ZnC@NC materials are irregular highly dispersed nanoparticles, and the Co 3ZnC@NC nanoparticles, through Figure 2 (e) and 2(f) of single Co 3 The ZnC@NC nanoparticles were observed, and it can be clearly seen that the larger Co 3 The ZnC@NC nanoparticles have a particle size of about 50-100 nm, and the Co 3 The ZnC particles are stably coated with an ultra-thin outer layer of nitrogen and carbon. Figure 2 Co in (f) 3 ZnC nanoparticles are locally enlarged to obtain Figure 2 (g) from Figure 2 (g) shows the lattice fringes on the nanoparticles. From the prominent lattice fringes in the figure, it can be measured that the lattice spacing of the nanoparticles is 0.264nm, corresponding to Co 3 The (1 1 0) crystal plane of ZnC crystal confirms that Co 3 The successful synthesis of ZnC@NC materials. 3 The element distribution of ZnC@NC composites was analyzed. Figure 2 (h)-2(l) It can be seen that Co, Zn, C, N, and O are all distributed in the nanoparticles. Co and Zn elements are evenly concentrated on the nanoparticles; while C and N elements are dispersed on the nanoparticles and have obvious aggregated distribution; O element is slightly distributed on the nanoparticles, indicating that Co 3 The ZnC@NC material is slightly oxidized. EDS spectrum analysis further confirms that the material Co 3 Composite of ZnC nanoparticles and NC layer.
[0099] Experimental Example 3 Discharge Specific Capacity Test
[0100] The assembly and testing methods of the lithium-sulfur battery described in this experimental example are as follows:
[0101] (1) Preparation of positive electrode: Ketjen black ECP-200L and sublimed sulfur were thoroughly ground and mixed in an agate mortar at a mass ratio of 1:3 for 15 min and placed in a porcelain boat. 2 In the atmosphere, keep the temperature at 155℃ for 12h, then keep the temperature at 200℃ for 30min, and the reaction is completed to obtain C / S composite material. 80wt% C / S, 10wt% Super P Li and 10wt% La133 (5wt% in water) are mixed evenly with deionized water as solvent and magnetically stirred for 12h, and then the obtained slurry is evenly coated on the surface of the carbon-coated layer of the carbon-coated aluminum foil by a scraper method. After vacuum drying, the obtained pole piece is cut into a disc with a diameter of 12mm to obtain a C / S pole piece.
[0102] (2) Assembly of button cells: The following operations were all carried out in a glove box filled with argon. The assembly of CR2032 button cells was performed using a lithium sheet as the negative electrode, a C / S sheet as the positive electrode, a modified separator as the separator (the separators prepared in Example 2 and Comparative Example 1 and PP were used as separators, respectively), and a LiTFSI electrolyte (1.0 mol / L LiTFSI in DME / DOL = 1:1 vol% with 1.0 wt% LiNO 3 , Suzhou Zhongyan Chemical Technology Co., Ltd.) is the electrolyte, and the amount of the electrolyte used is 30 μL for each battery.
[0103] (3) Test of the cycle stability of lithium-sulfur batteries: After the assembled button cells were left to stand for 12 hours, constant current charge and discharge tests were performed on them at different current densities using the Newwell battery test system. The operating voltage range of the battery was 1.7-2.8V.
[0104] A. The nitrogen-doped carbon-coated cobalt zinc carbide modified diaphragm (Co 3 The modified diaphragm of ZnC@NC / PP and the SuperP / PP prepared in Comparative Example 1 were assembled into a lithium-sulfur battery according to the above steps, and then the assembled lithium-sulfur battery was tested for electrical performance. The voltage curve of the 0.5C first charge and discharge platform obtained by the test was as follows: Figure 3 shown.
[0105] from Figure 3 It can be seen that Co 3 The first charge and discharge specific capacity of ZnC@NC / PP battery is higher than that of SuperP / PP and PP batteries, and it has a relatively low electrode polarization, indicating that Co 3 ZnC bimetallic carbide can effectively improve the capacity performance of lithium-sulfur batteries.
[0106] B. Nitrogen-doped carbon-coated cobalt zinc carbide modified diaphragm (Co 3 Comparison of the constant current charge-discharge curves of the first charge-discharge and the hundredth charge-discharge of the lithium-sulfur battery assembled with ZnC@NC / PP at 0.5C. Figure 4 shown.
[0107] from Figure 4 It can be seen that after 100 cycles, Co 3 The electrode polarization of the lithium-sulfur battery assembled with ZnC@NC / PP did not change much, indicating that Co 3 ZnC bimetallic carbide can effectively improve the electrochemical stability of lithium-sulfur batteries.
[0108] C. Co prepared in Example 2 3The EIS spectrum of the lithium-sulfur battery assembled with ZnC@NC / PP separator before cyclic charge and discharge is shown in Figure 5 (a) is shown; the CV curve at a scan rate of 0.1 mV / s is shown Figure 5 As shown in (b), the electrochemical properties of the material are further explored.
[0109] from Figure 5 (a) It can be clearly seen that after Co 3 The modification of ZnC@NC material significantly reduced the internal resistance of lithium-sulfur battery. 3 The charge transfer resistance of ZnC@NC / PP battery (Rct=24.2Ω) is much smaller than that of PP battery (Rct=47.5Ω), indicating that the modified Co 3 The ZnC@NC / PP separator layer can improve the charge transfer interface inside the battery, and by building a good conductive network structure on the cathode side separator, it can enhance the rapid transmission of electrons and ions on both sides of the separator. Therefore, the battery assembled with the separator of the present invention exhibits a lower battery internal resistance. The electrochemical redox reaction process of the battery was studied within the operating voltage range of the lithium-sulfur battery (1.7-2.8V) using a low scan rate voltammetric cycle test. Figure 5 In (b), at a scan rate of 0.1 mV / s, two obvious reduction peaks (around 2.35 V and 2.05 V) can be observed during the cathode reduction scan and a double peak (2.2-2.5 V) during the anodic oxidation scan. 3 The lithium-sulfur battery with ZnC@NC / PP as the separator has a stronger peak current, and the current response of the three redox peaks is significantly advanced, indicating that the Co prepared by the present invention 3 ZnC@NC composites can significantly improve the redox rate of lithium-sulfur electrochemical reactions and better catalyze the reversible reactions of LiPSs.
[0110] D. The nitrogen-doped carbon-coated cobalt zinc carbide modified diaphragm (Co 3 The rate performance of the lithium-sulfur battery assembled with ZnC@NC / PP) and PP separator was tested. The test results are as follows Figure 6 shown.
[0111] from Figure 6 It can be seen that Co 3The lithium-sulfur battery assembled with ZnC@NC / PP has a constant current discharge capacity of 1659.8 mA h / g at 0.1C, and constant current discharge capacity of 1246.9, 1136.7, 1047.3, 918.4, 823.4, 734.0 mA h / g at current densities of 0.2, 0.5, 1.0, 2.0, 3.0, and 5.0C, respectively. 3 The constant current discharge capacity of the lithium-sulfur battery assembled with ZnC@NC / PP can still be restored to 1201.7mA h / g. Compared with the lithium-sulfur battery assembled with PP (the capacity at 0.1C is 933.4mA h / g, and the capacity at 5.0C is 260.5mA h / g), Co 3 The lithium-sulfur battery assembled from ZnC@NC / PP has excellent rate performance. 3 The metal active sites of the ZnC@NC composites enable stable adsorption of LiPSs at different current densities, thus achieving high specific capacity at high current density.
[0112] E. The nitrogen-doped carbon-coated cobalt zinc carbide modified diaphragm (Co 3 The lithium-sulfur battery assembled with the SuperP / PP modified diaphragm prepared in Example 1 and the PP film was tested for cycle capacity and coulombic efficiency at a current density of 0.5C. The test results are shown in FIG. Figure 7 .
[0113] from Figure 7 It can be seen that Co 3 The initial discharge capacity of the lithium-sulfur battery assembled by ZnC@NC / PP was 1144.6 mA h / g, and after 100 cycles, the capacity was 962.6 mA h / g, with a capacity retention rate of 84.1%, which was better than SuperP / PP (initial charge and discharge 1003.6 mA h / g, capacity retention rate 79.6%) and PP-assembled lithium-sulfur battery (initial charge and discharge 635.1 mA h / g, capacity retention rate 61.6%). 3 ZnC bimetallic carbide can effectively improve the specific capacity performance and stability of lithium-sulfur batteries.
[0114] F. The nitrogen-doped carbon-coated cobalt zinc carbide modified diaphragm (Co 3 The lithium-sulfur battery assembled with ZnC@NC / PP was subjected to long cycle test. The battery cycle capacity and coulombic efficiency test results at 1.0C current density are shown in the figure. Figure 8 shown. Figure 8 It shows that Co 3Long-term cycling stability of ZnC@NC materials in lithium-sulfur batteries.
[0115] from Figure 8 It can be seen that the initial discharge capacity of the assembled lithium-sulfur battery reaches 996.6 mA h / g, and after 250 cycles of charge and discharge, the battery can still maintain a discharge capacity of 695.8 mA h / g. The coulombic efficiency of the lithium-sulfur battery is stable at more than 96%, the specific capacity maintenance rate is 69.8%, and the average attenuation rate per cycle is about 0.121%. This shows that the Co 3 ZnC@NC composite materials have a certain improvement effect on the cycle stability of lithium-sulfur batteries and show relatively good cycle performance.
[0116] When the sulfur loading of the cathode increases sharply to 6.2 mg / cm 2 (ie, E / S is 6 μL / mg), the corresponding Co 3 The lithium-sulfur batteries assembled with ZnC@NC / PP were tested at 0.2C ( Fig. 9 The test results of 50 cycles of 0.5C and 0.5C are as follows Fig. 9 As shown ( Fig. 9 under the following conditions).
[0117] from Fig. 9 It can be seen that even after 50 cycles, Co 3 The lithium-sulfur battery assembled with ZnC@NC / PP can maintain a discharge capacity of 805.4 mAh / g at 0.2C and a high discharge capacity of 542.8 mAh / g at 0.5C (areal capacity of ~5 mAh / cm 2 ). It shows that the Co 3 ZnC@NC composites are applied in lithium-sulfur batteries, which can endow the batteries with excellent cycling stability and have the potential to achieve high specific energy output using poor electrolytes.
[0118] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A nitrogen-doped carbon-coated cobalt zinc carbide catalyst material, characterized in that: The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material is prepared by stirring, standing aging, and high-temperature carbonization of potassium cobalt cyanide, a soluble orthodivalent cobalt salt, and a soluble orthodivalent zinc salt; The molar ratio of the soluble orthodivalent cobalt salt, the soluble orthodivalent zinc salt and potassium cobalt cyanide is 1:3-8:3-8.
2. The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material according to claim 1, characterized in that: The soluble ortho-cobalt salt is selected from one or more of Co(NO3)2·6H2O, CoCl2·6H2O, and Co(CH3COO)2·4H2O.
3. The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material according to claim 1, characterized in that: In step 1, The soluble positive divalent zinc salt is selected from one or more of Zn(NO3)2·6H2O, ZnCl2, and Zn(CH3COO)2·2H2O.
4. A method for preparing the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Step 1, adding potassium cobalt cyanide into water to obtain liquid A, adding a soluble ortho-divalent cobalt salt and a soluble ortho-divalent zinc salt into water to obtain liquid B, adding liquid B into liquid A, stirring at room temperature, and then standing for aging to obtain a nitrogen-doped carbon-coated cobalt zinc carbide material precursor; Step 2: The nitrogen-doped carbon-coated cobalt zinc carbide material precursor obtained in step 1 is centrifuged, washed, and vacuum dried in sequence, and then carbonized at high temperature under the protection of N2 atmosphere, and the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material is obtained after cooling.
5. The preparation method according to claim 4, characterized in that: In step 1, Slowly add liquid B into liquid A while stirring, with the volume ratio of liquid B to liquid A being 1:1, and continue stirring at room temperature for 5 to 20 minutes.
6. The preparation method according to claim 4, characterized in that: In step 1, The static aging time is 12 to 36 hours, and the static aging temperature is room temperature.
7. The preparation method according to claim 4, characterized in that: In step 2, The vacuum drying temperature is 50-70°C; The high temperature carbonization conditions are: under the protection of N2 atmosphere, heating to 600-800°C at a heating rate of 2-5°C / min, and then keeping at 600-800°C for 0.5-3h.
8. Use of the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material according to any one of claims 1 to 3 in the preparation of lithium-sulfur battery separators.
9. A lithium-sulfur battery separator, characterized in that: The lithium-sulfur battery separator is made of the nitrogen-doped carbon-coated cobalt zinc carbide catalyst material according to any one of claims 1 to 3.
10. The lithium-sulfur battery separator according to claim 9, characterized in that The lithium-sulfur battery separator is prepared by the following steps: The nitrogen-doped carbon-coated cobalt zinc carbide catalyst material, the conductive agent and the binder are added into the solvent and stirred evenly, the obtained slurry is evenly coated on the diaphragm, and then vacuum dried to obtain the lithium-sulfur battery diaphragm.
Citation Information
Patent Citations
A method for preparing a modified separator for lithium-sulfur batteries
CN112886134B
Nitrogen-doped carbon layer coated cobalt manganese carbide composite material and application thereof
CN111617790A
Application of nitrogen-doped carbon-coated Co and / or Co3ZnC composite material in preparation of lithium-sulfur battery diaphragm
CN112670669A
Cited By
Synthesis process of basic cobalt carbonate
CN121698393A